2015
DOI: 10.1002/2015ja021196
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of energetic particle precipitation effects during the 2003–2004 Arctic winter

Abstract: Energetic particle precipitation (EPP) during the 2003–2004 Arctic winter led to the production and subsequent transport of reactive odd nitrogen (NOx = NO + NO2) from the mesosphere and lower thermosphere (MLT) into the stratosphere. This caused NOx enhancements in the polar upper stratosphere in April 2004 that were unprecedented in the satellite record. Simulations of the 2003–2004 Arctic winter with the Whole Atmosphere Community Climate Model using Specified Dynamics (SD‐WACCM) are compared to satellite m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 81 publications
10
77
0
Order By: Relevance
“…The adjusted descent rates for the 2004 event are also in good agreement with previous estimates of the vertical component of the meridional circulations using MIPAS temperatures and diabatic heating rates (Randall et al, 2015). During both events, the descent rates decrease rapidly towards the stratopause, where they take values of around 200 m day −1 .…”
Section: Parameterization For Elevated Stratopause Eventssupporting
confidence: 76%
See 1 more Smart Citation
“…The adjusted descent rates for the 2004 event are also in good agreement with previous estimates of the vertical component of the meridional circulations using MIPAS temperatures and diabatic heating rates (Randall et al, 2015). During both events, the descent rates decrease rapidly towards the stratopause, where they take values of around 200 m day −1 .…”
Section: Parameterization For Elevated Stratopause Eventssupporting
confidence: 76%
“…The negative trend in the geomagnetic activity level is closely related to the reduction of solar cycle amplitudes encountered for cycles 23 and 24. As the decline of solar activity is expected to continue in the coming decades (Steinhilber and Beer, 2013), this is likely to affect the long-term NO y trend by counteracting the expected increase caused by growing N 2 O emissions (Ravishankara et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The downward transport of nitrogen oxide (NO), produced at around 110 km through energetic particle precipitation (EPP) events (e.g. Barth and Bailey, 2004;Randall et al, 2005Randall et al, , 2007Randall et al, , 2015, garners particular attention because NO x (NO + NO 2 ) catalytically destroys ozone in the stratosphere. Periods of strong atmospheric descent are known to coincide with the timing of sudden stratospheric warmings (SSWs; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using the KArlsruhe SImulation Model of the middle Atmosphere (KASIMA) with specified dynamics below 48 km and prescribed NO x concentrations from MIPAS night-time NO 2 observations above 55 km, Reddmann et al (2010) calculated the amount of EPP-NO x entering the stratosphere from July 2002 to March 2004. KASIMA reproduced the MIPAS observations of NO x entering the stratosphere reasonably well, even during the SSW winter 2003/2004.…”
Section: Introductionmentioning
confidence: 99%
“…They found that non-orographic GWD is primarily responsible for driving the circulation that results in the descent of CO from the thermosphere following the warmings. Randall et al (2015) investigated the NO x descent during the Arctic winter/spring of 2004 with Whole Atmosphere Community Climate Model (WACCM) simulations that were nudged to Modern-Era Retrospective Analysis for Research and Applications (MERRA) data. They found that their simulated NO x , although qualitatively reproducing the enhanced descent after the ES event, was up to a factor of 5 too low compared with satellite observations.…”
Section: Introductionmentioning
confidence: 99%